CSIG-24. miR-575 IS ASSOCIATED WITH WORSE SURVIVAL OF GBM PATIENTS AND ACTS AS A NOVEL ONCOGENE THROUGH TARGETING p27/CDKN1B AND BLID/BRCC2. (5th November 2018) - Cui, Tiantian; Gray, Ashley; Hlavin Bell, Erica; McElroy, Joseph; Geurts, Marjolein; Meng, Wei; Haque, Jahar; Robe, Pierre; Chakravarti, Arnab
Abstract: Glioblastoma (GBM) patients currently face poor survival outcomes with an average survival period of less than 15 months, while only 3–5% of patients survive longer than 36 months. Although the mechanisms of tumorigenesis are still being elucidated, miRNAs are promising candidates to explore as novel and prognostic biomarkers in GBM. Here, we determined the correlation between miR-575 expression in GBM tumors and overall survival (OS) of patients and undertook functional studies to unfold the contribution of this miR to GBM tumorigenesis. Total RNAs were isolated from 268 FFPE GBM tumor samples and miR expression was assayed (simultaneously) using NanoString Technologies, and univariable and multivariable cox regression analyses were performed. Cell proliferation, colony formation, migration assay, qPCR, immunoblotting, and luciferase assay were conducted to define the function of miR-575 in GBM. Our survival analysis (n=268) show that miR-575 is associated with worse OS of GBM patients (HR=1.5, p-value=5.77E-05) by continuous UVA. miR-575 was also found to be significantly associated with OS, independent of age, gender, treatment, and KPS in a MVA (HR=1.208, p=0.012). Since miR-575 was found to be negatively associated with OS, we hypothesized that miR-575 overexpression would increase tumor progression. Our functional studies indicate that overexpression of miR-575 significantly increased the proliferation and motility of LN229 and U251 GBM cells in vitro . Consistent with the result found in LN229 and U251 cells, inhibition of miR-575 in U87 cells significantly decreased their proliferation and motility. Subsequent in silico and mechanistic studies identified p27/CDKN1B and BLID/BRCC2 aspotential target genes of miR-575 in GBM. Overexpression of miR-575 in GBM cells reduced the expression of both BLID and p27 at both mRNA and protein levels. miR-575 has prognostic value in GBM, with higher expression correlating with worse OS of patients, and contributes to GBM tumorigenesis by inhibiting expression of p27 and BLID .